'Scuse me while I kiss this guy, and other misheard lyrics - Edwards, Gavin, 1968- (Simon & Schuster, 1995)
Contains over one-hundred song lyrics that have been misheard from the mid 1960s to the late 1990s, including the lyrics people thought they heard, and what the lyrics really are.